2011
DOI: 10.1080/0312407x.2011.606909
|View full text |Cite
|
Sign up to set email alerts
|

Social Work in the Emergency Department—Implementation of a Domestic and Family Violence Screening Program

Abstract: Women who have experienced domestic and family violence use health services more frequently than women who have not. Early identification and intervention by the health system may reduce health problems associated with domestic and family violence and lead to savings for the health sector. This study aimed to evaluate the impact of a new domestic and family violence screening program, which was based on an ecological model and introduced by a social work team in the Emergency Department of a major metropolitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…There are relatively few studies in Australasian hospital EDs focusing on the experience of health professionals caring for women with IPV. Some research has evaluated education and institutional protocols to assist clinicians to identify and respond to IPV and has demonstrated improved clinician knowledge, assessment, and referral practices up to 6 months postimplementation. Another study surveyed ED staff about screening practices, finding that medical officers and nurses lack knowledge and capacity to identify and respond to IPV.…”
mentioning
confidence: 99%
“…There are relatively few studies in Australasian hospital EDs focusing on the experience of health professionals caring for women with IPV. Some research has evaluated education and institutional protocols to assist clinicians to identify and respond to IPV and has demonstrated improved clinician knowledge, assessment, and referral practices up to 6 months postimplementation. Another study surveyed ED staff about screening practices, finding that medical officers and nurses lack knowledge and capacity to identify and respond to IPV.…”
mentioning
confidence: 99%
“…Role legitimacy and perceived self‐efficacy have been identified as vital to a positive therapeutic attitude towards harmful drinking patients . Previous research has also found experience, knowledge and confidence were the keys to clinicians regularly screening for interpersonal violence . Effective training and use of best evidence has long been established as improving patient outcomes , while best practice activities such as alcohol screening and brief intervention can reduce rates of harmful alcohol consumption and identify patients most at risk .…”
Section: Introductionmentioning
confidence: 99%
“…Research to date indicates that women are not being routinely screened for DV by all HCPs [ 27 , 28 ]. The reluctance of HCPs to screen for DV is purported to be due to inadequate knowledge and training with DV screening tools and the belief that resources to support identified victims are inadequate [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research to date indicates that women are not being routinely screened for DV by all HCPs [ 27 , 28 ]. The reluctance of HCPs to screen for DV is purported to be due to inadequate knowledge and training with DV screening tools and the belief that resources to support identified victims are inadequate [ 27 , 28 ]. Furthermore, HCPs’ lack of DV screening has been identified as due to fear of offending patients, a lack of time and forgetting to routinely screen, a lack of patient privacy, workload issues, reluctance to see DV as a health issue, and HCPs’ personal discomfort with DV [ 27 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation